2011
DOI: 10.1007/s13238-011-1018-1
|View full text |Cite
|
Sign up to set email alerts
|

Structure and function of WD40 domain proteins

Abstract: The WD40 domain exhibits a β-propeller architecture, often comprising seven blades. The WD40 domain is one of the most abundant domains and also among the top interacting domains in eukaryotic genomes. In this review, we will discuss the identification, definition and architecture of the WD40 domains. WD40 domain proteins are involved in a large variety of cellular processes, in which WD40 domains function as a protein-protein or protein-DNA interaction platform. WD40 domain mediates molecular recognition even… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
484
0
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 543 publications
(524 citation statements)
references
References 82 publications
10
484
0
6
Order By: Relevance
“…2C), six of which are composed of four β-strands, with the last β-sheet containing only three ordered strands; the first 12 and last 13 residues are disordered and not visible in the electron density. The structure therefore lacks the "velcro" closure seen in the majority of WD40 domains, where the three strands from the last blade form a β-sheet with the strand that precedes the first blade (22,37). The sequence motifs that characterize the WD40 domain are scarce in MEP50, with only two of the seven blades containing the WD motif at the end of the third strand.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2C), six of which are composed of four β-strands, with the last β-sheet containing only three ordered strands; the first 12 and last 13 residues are disordered and not visible in the electron density. The structure therefore lacks the "velcro" closure seen in the majority of WD40 domains, where the three strands from the last blade form a β-sheet with the strand that precedes the first blade (22,37). The sequence motifs that characterize the WD40 domain are scarce in MEP50, with only two of the seven blades containing the WD motif at the end of the third strand.…”
Section: Resultsmentioning
confidence: 99%
“…WD40 proteins are known to play vital roles in various cellular networks (20,21). These proteins function as protein-protein and protein-DNA interaction platforms and also as recognition modules of posttranslational modifications (22,23). Recent studies on MEP50 identified the presence of two nuclear exclusion signals and three nuclear localization signals that control its subcellular localization and its function as a transcriptional cofactor of androgen receptor during prostate development and tumorigenesis (24).…”
mentioning
confidence: 99%
“…48 WD40 domains exist in a wide variety of eukaryotic proteins and typically form a seven bladed bpropeller structure to which proteins can bind either stably or reversibly. 53 Most likely, the WD40 domain of ALFY can form a complete b-propeller structure without having seven WD40 repeats, but it also possible that WD40 repeats need to be donated from other interaction partners to complete the b-propeller. Finally, ALFY contains a PH-like domain followed by a BEACH domain.…”
Section: Adaptor Proteinsmentioning
confidence: 99%
“…The blades assemble to form a toroidally shaped structure with a solvent accessible central channel, where one side of the toroid is wider ("wide" side) than the other side ("narrow" side). In general, the surfaces of the wide and narrow sides contain loops that connect the β strands and are important for either protein-protein or proteinnucleic acid interactions (27). Similar to other β-propellers, the N and C termini of Dos1WD come together to form the last blade, known as the "velcro closure," which has been shown to stabilize the β-propeller (27).…”
Section: Wd Repeat Domain Of Dos1mentioning
confidence: 99%
“…S3). Because the loops on the β-propellers are frequently involved in target recognition (27), these disordered and flexible loops on the narrow side of Dos1WD are expected to be important for Dos1 function.…”
Section: Wd Repeat Domain Of Dos1mentioning
confidence: 99%